LIETUVOS NACIONALINĖS MARTYNO MAŽVYDO BIBLIOTEKOS RETŲ KNYGŲ IR RANKRAŠČIŲ SKYRIAUS PALEOTIPŲ RINKINYS - VAITKEVIČIŪTĖ, VIKTORIJA (Knygotyra, 2011)
Lietuvos nacionalinė Martyno Mažvydo bibliotekaGedimino pr. 51, LT-01504 Vilnius, LietuvaEl. paštas: viktorija.vait@gmail.comStraipsnyje nagrinėjami Lietuvos nacionalinės Martyno Mažvydo bibliotekos Retų knygų ir rankraščių skyriaus paleotipai: jų leidimo vieta, spaustuvininkai, tematika bei proveniencijos, dėmesį telkiant į retesnius, Lietuvos knygos kultūrai svarbesnius leidinius. Iš šiame skyriuje saugomų daugiau kaip 800 paleotipų analizuojama tik dalis jų, nes daugiau negu 200 knygų teturi kortelinį bibliografinį aprašą ir išsamiai juos ištirti šiuo metu neįmanoma. Dalies šių paleotipų analizė papildo jau esamus tyrimus, praplečia senosios knygos kultūros vaizdą.Reikšminiai žodžiai: knygotyra, paleotipai, retos knygos, spaustuvininkai, proveniencijos.THE COLLECTION OF POST-INCUNABULA IN THE MARTYNAS MAŽVYDAS NATIONAL LIBRARY OF LITHUANIAViktorija VAITKEVIČIŪTĖAbstractPost-incunabula or the books printed in the first half of the 16th century (from January 1, 1501 to January 1, 1551), along with incunabula, are considered to be the oldest and most valuable publications in the world. Due to their likeness to incunabula and publishing specifics, post-incunabula are considered to be historical treasures and monuments of culture. The Rare Book and Manuscript Department of the National Library of Lithuania has in its holdings more than 800 post-incunabula, not including the ones kept at the Department of the National Archival Fund of Published Documents. The exact number is still unknown, since not all the books have been included into the electronic catalogue: more than 200 of them have only a card catalogue description and are awaiting a more detailed study. This article analyses specific features of part of the post-incunabula collection in the NLL Rare Book and Manuscript Department: their place of publication, publishers, thematics and provenances. Principal attention is accorded to the books that are rarer, more interesting and more important for Lithuania’s culture and book culture in general.The most of the post-incunabula kept in the Rare Book and Manuscript Department were published in Germany, many in Switzerland, France and Italy. There also is a small number of post-incunabula published in Poland (Cracow). Of the publications produced by Cracow’s printers, the article discusses those by Jan Haller (ca. 1467–1525), Hieronim Wietor (ca. 1480–1546) and Florian Ungler (d. 1536). It is necessary to mention Aldines – the publications by one of themost famous European printers, Aldo Manuzio (Lat. Aldus Manutius; ca. 1450–1515) and by his descendants. The article also touches upon the work of such acclaimed French publishers as Henri Estienne (lat. Henricus Stephanus, ca. 1460–1520), founder of the famous dinasty of printers, and the Lyonese printer Sébastien Gryphius (ca. 1493–1556). The Rare Book and Manuscript Department also keeps quite a few post-incunabula published by Johannes Frobenof Basel (1460–1537).As to the content aspect, the collection of post-incunabula in the department is versatile. For the most part, it is made up by religious literature: sermons, bibles, theological treatises, Church Fathers’ writings. There are many works by and commentaries on classical authors, of whom Cicero, at the time of the Renaissance viewed as the greatest authority on rhetoric, is the most famous one. The post-incunabula collection illuminates the emergence of the Reformations and the related spread of new ideas in the first half of the XVIth century. The Rare Book and Manuscript Department boasts a number of works by the founder of Protestantism, Martin Luther (1483–1546) and by the most acclaimed humanist of the times, Desiderius Erasmus (1469–1536).The provenances in the post-incunabula (manuscript inscriptions, stamps, bookplates) provide much interesting information. Most often found are ownership marks of the establishments that since the olden times had been preserving books: various monasteries, churches and priest seminaries,. The notable representative of the post-incunabulum culture is the Bernardine Order. According to the electronic catalogue, the Rare Book and Manuscript Departmenthas in its holdings 21 post-incunabula formerly kept by the library of the Tytuvėnai Bernardine Monastery. Most provenance inscriptions are from Kaunas Priest Seminary, the library of the Samogitian Priest Seminary, the library of the Vilnius Seminary and Kražiai College. Of the XIXth century personal libraries,particularly noteworthy are the collections of Jonas Krizostomas Gintila (1788–1857), XIXth-century bibliophile, hebraist and administrator of the Samogitian Diocese, and of Friedrich August Gotthold (1778–1858), educator and music theorist. A separate, rather abundant group of provenance inscriptions consists of the books that formerly belonged to Königsberg University. An in-depth study of all the post-incunabula kept in the NLL would significantly add to the existing research and broaden the understanding of old book culture.